2021
DOI: 10.3389/fphys.2021.652579
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA as Potential Biomarkers of Platelet Function on Antiplatelet Therapy: A Review

Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs, able to regulate cellular functions by specific gene modifications. Platelets are the major source for circulating miRNAs, with significant regulatory potential on cardiovascular pathophysiology. MiRNAs have been shown to modify the expression of platelet proteins influencing platelet reactivity. Circulating miRNAs can be determined from plasma, serum, or whole blood, and they can be used as diagnostic and prognostic biomarkers of platelet reactivity during antipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 133 publications
(198 reference statements)
0
40
0
Order By: Relevance
“…Although we cannot exclude the possibility that this could be partly because of platelet contamination or lysis, among a list of 11 miRNAs previously reported to strongly correlate with platelet contamination (Mitchell et al, 2016) only two (hsa-miR-93-5p and hsa-miR-17-5p) correlated with platelets in more than one severity group in our study. Alternatively, as platelet-secreted miRNAs reflect platelet activation and function (Czajka et al, 2021), severity group-specific platelet-associated miRNA signatures could provide novel insight into the observed thrombocytopenia and platelet aggregation phenotype in severe COVID-19 (Lippi et al, 2020;Rampotas and Pavord, 2020).…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…Although we cannot exclude the possibility that this could be partly because of platelet contamination or lysis, among a list of 11 miRNAs previously reported to strongly correlate with platelet contamination (Mitchell et al, 2016) only two (hsa-miR-93-5p and hsa-miR-17-5p) correlated with platelets in more than one severity group in our study. Alternatively, as platelet-secreted miRNAs reflect platelet activation and function (Czajka et al, 2021), severity group-specific platelet-associated miRNA signatures could provide novel insight into the observed thrombocytopenia and platelet aggregation phenotype in severe COVID-19 (Lippi et al, 2020;Rampotas and Pavord, 2020).…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…Platelets are found to be a significant source of miRNAs, small (18–25 nucleotides), non-coding RNAs, that influence various aspects of cellular functions through the regulation of gene expression. A single miRNA can influence the expression of multiple genes, and one single target can be regulated by several miRNAs [ 9 , 10 ]. Circulating miRNAs can be detected in many body fluids including plasma, serum, or whole blood, and they are stable in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they can be used as diagnostic and prognostic novel biomarkers as well as novel therapeutic targets [ 11 , 12 ]. Due to the number of limitations of currently used platelet function tests, circulating miRNAs could be promising biomarkers of inflammation and platelet function and were previously described to participate in processes of platelet activation and aggregation [ 9 , 13 ]. Alteration in their expression is associated with various biological processes, including platelet reactivity, glucose metabolism, antiplatelet drug response, and anti-inflammatory response [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that blood platelets express a vast amount of miRNAs that control their functions and reactivity [ 12 ]. Moreover, platelets contain all necessary protein enzymes delivered from megakaryocytes to convert pre-miRNA to mature sequences [ 13 ], thus constituting an excellent area for miRNA evaluation.…”
Section: Introductionmentioning
confidence: 99%